2016
DOI: 10.1186/s12889-016-3368-3
|View full text |Cite
|
Sign up to set email alerts
|

Individual, social, and environmental influences on the transitions in physical activity among emerging adults

Abstract: BackgroundYouth’s physical activity (PA) may change across developmental periods. Although previous studies have observed a decline in levels of PA during adolescence, few studies have explored trends in PA during the transition from adolescence to young adulthood and what factors may impact the transitional change. The purpose of this study was to examine changes and predictors of change over time in PA from 10th grade to post-high school.MethodsThe NEXT Generation Health Study recruited a nationally-represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Stratified meta‐analysis showed that the decrease in MVPA was larger for males (−16.35 [−30.34, −2.35] min/day of MVPA) than for females (−6.61 [−14.90, 1.67] min/day of MVPA). Of the remaining three studies, which could not be included in the meta‐analysis, all reported declines in physical activity over the transition out of high school . Visual inspection of funnel plot asymmetry and Egger's test for bias suggested no evidence of asymmetry in the meta‐analysis ( P =.84) and therefore no evidence of publication bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stratified meta‐analysis showed that the decrease in MVPA was larger for males (−16.35 [−30.34, −2.35] min/day of MVPA) than for females (−6.61 [−14.90, 1.67] min/day of MVPA). Of the remaining three studies, which could not be included in the meta‐analysis, all reported declines in physical activity over the transition out of high school . Visual inspection of funnel plot asymmetry and Egger's test for bias suggested no evidence of asymmetry in the meta‐analysis ( P =.84) and therefore no evidence of publication bias.…”
Section: Resultsmentioning
confidence: 99%
“…These studies both reported that those continuing to college/university experienced a smaller decrease in MVPA compared with those not continuing in education . However, a further study, which could not be included in the meta‐analysis due to its dichotomized outcome, reported higher odds of meeting PA recommendations among those not attending college/university following high school compared with those attending college/university …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 The analyses of the association of self-reported MVPA with environmental variables and time-varying covariates in the NEXT full sample found that compared with those attending 4-year colleges or living on campus, participants not attending school or attending community-college level schools, and living at home or in own place were more likely to meet MVPA recommendations (at least 60 minutes per day over the past 7 days). The inconsistencies between the 2 studies are likely attributable to the use of self-reported versus objectively measured physical activity.…”
Section: Discussionmentioning
confidence: 99%